An investigation into strategies of translating metaphors and similes in “the thorn birds” by colleen mcculough into Vietnamese - Trần Văn Vỹ (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This paper investigates the strategies of translating metaphors and similes from English into Vietnamese, adopting the framework of metaphor translation proposed by Newmark (1988). The study attempts to find out the strategies used in rendering metaphors and similes in two translated versions. The data of the study were collected from the famous novel “The Thorn Birds” by Colleen McCulough, and its two Vietnamese translational versions: “Tiếng chim hót trong bụi mận” by Phạm Mạnh Hùng and “Những con chim ẩn mình chờ chết” by Trung Dũng. The study figures out the occurrence frequency of seven strategies and the factors affecting the choice of each strategy. It also clarifies the similarities and differences between the rendering of metaphors and similes across English and Vietnamese in the two versions. Although the applications of seven strategies in the two versions are different, it can be inferred that both translators could have made successful attempts in maintaining the equivalent effect in metaphor translation. The results accordingly have provided practical implications for the teaching and learning of English in general, and for the work of translation, in particular.